Experimental investigation of sandwich glazed solar photovoltaic module. (2020) - Veeramanikandan, M.; Arjunan, T.V.; Jidhesh, P.
Abstract: The light and heat energies from the sun are directly converted into electricity either by directly using solar photovoltaic (SPV) module or indirectly using concentrated solar technology system. Photovoltaic (PV) cells is a semiconductor device which is sensitive to temperature. The energy gap of the silicon material reduces when its temperature increases. The decrease in the energy gap of the silicon semiconductor with increasing working temperature can affect the performance of the PV cell. In this article, the working temperature of commercial grade silicon-based solar photovoltaic module as well as sandwich glazed solar photovoltaic module and its impact upon the electricity delivered is discussed. The significant effects of operating temperature, irradiation and wind speed on the PV module temperature were presented. These parameters were used to estimate the electrical performance of the commercial and sandwich glazed PV modules.